Achieving legitimacy through co-operative governance and social and environmental disclosure by credit unions in a developing country. Issue 2 (8th May 2017) - Mathuva, David M.; Mboya, Josephat K.; McFie, James B.
Abstract : Purpose: The purpose of this paper is to utilize legitimacy theory to test the association between the governance of credit unions and their social and environmental disclosure in a developing country, Kenya. A further examination of institutional pressures due to regulatory forces on the association between co-operative governance and credit union social and environmental disclosure (CSED) is performed. Design/methodology/approach: Using a sample comprising of 1, 272 credit union observations over the period 2008-2013, panel OLS regressions are performed to establish the association between co-operative governance and CSED. A comparison of the pre- and post-regulatory influences on co-operative governance and CSED is also performed. Findings: The findings, which are in support of both legitimacy and institutional theories, depict a positive and significant association between co-operative governance and CSED. The significance of the co-operative governance score improves from the pre-regulation period to the post-regulation period. Other significant variables influencing the volume of CSED by credit unions in Kenya include credit union size and financial performance as measured by the return on assets. Research limitations/implications: The study examines CSED practices in a developing country and in organizations in a single sector. Further, CSED is measured using a self-constructed index with data being obtained from audited annual reports only. Practical implications: The study highlights the need to develop CSED guidelines tailored for credit unions, and a focus on co-operative governance as a way of improving disclosure practices. Originality/value: The study utilizes a sector-specific governance variable and a CSED index to examine the association between the two variables by credit unions in a developing country. The study also attempts to investigate the role of regulation on the association between co-operative governance and the volume of CSED.